2023
DOI: 10.1038/s41598-023-30702-z
|View full text |Cite
|
Sign up to set email alerts
|

Size distribution and relationship of airborne SARS-CoV-2 RNA to indoor aerosol in hospital ward environments

Abstract: Aerosol particles proved to play a key role in airborne transmission of SARS-CoV-2 viruses. Therefore, their size-fractionated collection and analysis is invaluable. However, aerosol sampling in COVID departments is not straightforward, especially in the sub-500-nm size range. In this study, particle number concentrations were measured with high temporal resolution using an optical particle counter, and several 8 h daytime sample sets were collected simultaneously on gelatin filters with cascade impactors in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…Indoor dust monitoring in environments such as hospital wards, public indoor spaces, and public transport vehicles has the potential to complement wastewater surveillance, especially in areas with a small number of infected individuals, where it is crucial to identify specific outbreaks. 14 , 20 , 29 , 30 , 31 , 32 , 33 Recent studies have shown that indoor dust in rooms where infected individuals were present contains detectable levels of SARS-CoV-2, suggesting that monitoring SARS-CoV-2 in indoor dust could effectively detect COVID-19 outbreaks. 14 , 30 , 31 However, the relationship between the concentration of SARS-CoV-2 RNA found in dust and the incidence of COVID-19 cases in the community is still inadequately explored.…”
Section: Introductionmentioning
confidence: 99%
“…Indoor dust monitoring in environments such as hospital wards, public indoor spaces, and public transport vehicles has the potential to complement wastewater surveillance, especially in areas with a small number of infected individuals, where it is crucial to identify specific outbreaks. 14 , 20 , 29 , 30 , 31 , 32 , 33 Recent studies have shown that indoor dust in rooms where infected individuals were present contains detectable levels of SARS-CoV-2, suggesting that monitoring SARS-CoV-2 in indoor dust could effectively detect COVID-19 outbreaks. 14 , 30 , 31 However, the relationship between the concentration of SARS-CoV-2 RNA found in dust and the incidence of COVID-19 cases in the community is still inadequately explored.…”
Section: Introductionmentioning
confidence: 99%